CIVIL SERVICE MANAGEMENT THROUGH THE EYES OF ‘ROOKIES’ AND EXPERIENCED OFFICIALS - Roman K. Ovcharenko (Advanced Engineering Research, 2012)
Some results of the opinion survey conducted with the aim of studying attitude of the civil servants towards the civil service reforming processes, the formation of the civil service management system, and of revealing the interrelations between the functioning of civil service management system and the changing of the working conditions for officials, of researching the civil servants’ opinion on the effectiveness of the regional body of the civil service management, are described. The data are presented depending on the length of the civil service of the respondents.